Tropical insect diversity: evidence of greater host specialization in seed‐feeding weevils - Guille Peguero; Raúl Bonal; Daniel Sol; Alberto Muñoz; Victoria L. Sork; Josep M. Espelta (Ecology, 2017)
Host specialization has long been hypothesized to explain the extraordinary diversity of phytophagous insects in the tropics. However, addressing this hypothesis has proved challenging because of the risk of over‐looking rare interactions, and hence biasing specialization estimations, and the difficulties to separate the diversity component attributable to insect specialization from that related to host diversity. As a result, the host specialization hypothesis lacks empirical support for important phytophagous insect clades. Here, we test the hypothesis in a radiation of seed‐feeding insects, acorn weevils ( Curculio spp.), sampled in temperate and tropical regions (California and Nicaragua, respectively) with an equivalent pool of oak host species. Using DNA sequences from three low‐copy genes, we delimited to species level 778 weevil larvae extracted from host seeds and assessed their phylogenetic relationships by Maximum Likelihood and Bayesian inference. We then reconstructed the oak‐weevil food webs and examined differences in alpha, beta and gamma diversity using Hill numbers of effective species. We found a higher alpha, beta and gamma diversity of weevils in Nicaragua compared to California despite similar richness of host species at both local and regional level. By means of Bayesian mixed models, we also found that tropical weevil species were highly specialized both in terms of host range and interaction strength, whereas their temperate congeners had a broader taxonomic and phylogenetic host spectrum. Finally, in Nicaraguan species, larval body size was highly correlated with the size of the acorns infested, as would be expected by a greater host specialization, whereas in California this relationship was absent. Altogether, these lines of evidence support the host specialization hypothesis and suggest contrasting eco‐evolutionary dynamics in tropical and temperate regions even in absence of differences in host diversity.